2010
DOI: 10.1371/journal.pone.0015071
|View full text |Cite
|
Sign up to set email alerts
|

Polyamines Are Present in Mast Cell Secretory Granules and Are Important for Granule Homeostasis

Abstract: BackgroundMast cell secretory granules accommodate a large number of components, many of which interact with highly sulfated serglycin proteoglycan (PG) present within the granules. Polyamines (putrescine, spermidine and spermine) are absolutely required for the survival of the vast majority of living cells. Given the reported ability of polyamines to interact with PGs, we investigated the possibility that polyamines may be components of mast cell secretory granules.Methodology/Principal FindingsSpermidine was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
45
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 51 publications
(48 citation statements)
references
References 59 publications
3
45
0
Order By: Relevance
“…Mice (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) wk old) were all on C57BL/6J genetic background, and all animal experiments were approved by the local ethical committee. mM NaCl, 5 mM KCl, 1.4 mM CaCl 2 , 1 mM MgCl 2 , 5.6 mM glucose, 10 mM HEPES, and 0.1% BSA [pH 7.4]) and stimulated with TNP-OVA (0.4 mg/ml).…”
Section: Micementioning
confidence: 99%
See 1 more Smart Citation
“…Mice (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18) wk old) were all on C57BL/6J genetic background, and all animal experiments were approved by the local ethical committee. mM NaCl, 5 mM KCl, 1.4 mM CaCl 2 , 1 mM MgCl 2 , 5.6 mM glucose, 10 mM HEPES, and 0.1% BSA [pH 7.4]) and stimulated with TNP-OVA (0.4 mg/ml).…”
Section: Micementioning
confidence: 99%
“…Granule-enriched fractions were obtained from BMMCs by soft disruption in a bath sonicator and density centrifugation in Percoll, as previously described (10).…”
Section: Preparation Of Granule-enriched Fractionsmentioning
confidence: 99%
“…However, recent studies have shown that the polyamines spermine and spermidine are an essential part of the granule component of mast cells, and play an essential role in the biogenesis and homeostasis of these organelles [Garcia‐Faroldi et al, 2010]. We have previously shown that mast cells are a critical component of HO and when these cells are eliminated HO is severely inhibited [Salisbury et al, 2011].…”
Section: Discussionmentioning
confidence: 99%
“…These polyamines are stored in mast cell secretory granules, appear in the extracellular space through A23187-evoked Ca 2ϩ -dependent processes, and are thought to be involved in biogenesis and homeostasis of secretory granules (4). Furthermore, it has been reported that spermine and spermidine, when applied to mast cells extracellularly, facilitate synthesis and release of histamine from mast cells (7)(8)(9)(10)(11).…”
mentioning
confidence: 99%
“…Furthermore, it has been reported that spermine and spermidine, when applied to mast cells extracellularly, facilitate synthesis and release of histamine from mast cells (7)(8)(9)(10)(11). Spermine and spermidine are also involved in storage and/or release of histamine and serotonin in the mast cell granules (4,12). Although there are numerous studies on polyamine function in mast cells, it remains unclear how these polyamines are loaded into mast cell granules and discharged into the extracellular space upon stimulation.…”
mentioning
confidence: 99%